Serotonin and Its Receptor as a New Antioxidant Therapeutic Target for Diabetic Kidney Disease - Yu Yang; Hui Huang; Zheng Xu; Jun-kai Duan (Journal of Diabetes Research)
Diabetic kidney disease (DKD) is a widespread chronic microvascular complication of diabetes mellitus (DM), affects almost 30–50% of patients, and represents a leading cause of death of DM. Serotonin or 5-hydroxytryptamine (5-HT) is a multifunctional bioamine that has crucial roles in many physiological pathways. Recently, emerging evidence from experimental and clinical studies has demonstrated that 5-HT is involved in the pathogenesis of diabetic vascular complications. The 5-HT receptor (5-HTR) antagonists exert renoprotective effects by suppressing oxidative stress, suggesting that 5-HTR can be used as a potential target for treating DKD. In this review, therefore, we summarize the published information available for the involvement of 5-HT and 5-HTR antagonists in the pathogenesis of various diabetic complications with a particular focus of DKD. We conclude that 5-HTR is a potential therapeutic target for treating DKD, as it has been successfully applied in animal models and has currently being investigated in randomized and controlled clinical trials.